Rancang Bangun Aplikasi Pemeliharaan Alat Menggunakan QR-Code (Studi Kasus Telkom Property Surabaya Utara) - Dhimas Bintang Bagaskara; Bagus Kurniawan; Mohammad Sholik; Fidi Wincoko Putro; Ardian Yusuf Wicaksono; Titus Kristanto; Amirah Diandra (Journal of Computer System and Informatics (JoSYC), 2022)
Telkom Property North Surabaya has a responsibility in terms of maintaining and maintaining equipment for all assets of the Telkom Indonesia company in the North Surabaya and Madura areas. Previously, tool maintenance records were written manually, but the Mei-V application has an impact because now tool maintenance recording can be done through an android application by scanning a QR-Code. The Mei-V application was created with the aim of providing a solution so that equipment maintenance records can be carried out through an application that is connected to a direct database. The application uses the Spiral Model method so that it can carry out continuous development in the form of adding functions or changes to suit existing needs. The result of implementing the Spiral Model that can be felt is the flexibility of application development because it can always be monitored and improved at any time. The Mei-V application can provide various useful information for maintenance activities, including detailed information on equipment maintenance, maintenance reports that can be downloaded by supervisors. The Mei-V application testing was carried out with two test methods. Functionality testing is carried out with details of 4 test scenarios and shows a 100% success percentage. While the Usage Test conducted on 5 respondents showed positive results with details of the average score scale of 3.8 out of 5 points.